Catalytic Asymmetric Dearomative [3+2] Cyclisation of 1, 4‐Quinone with 2, 3‐Disubstituted Indoles. Issue 23 (30th October 2019) - Zhang, Lvye; Hu, Jinjin; Xu, Ruigang; Pan, Shulei; Zeng, Xiaofei; Zhong, Guofu
Abstract: A chiral phosphoric acid‐catalysed asymmetric dearomative [3+2] cyclisation for accessing enantioenriched benzofuroindolines with two vicinal tetrasubstituted carbon centres from readily available 1, 4‐quinone and 2, 3‐disubstituted indoles is developed. This protocol distinguishes itself by availability of the starting materials and mild reaction conditions in a stereoselective manner, which provides a complement to the existing methods for the asymmetric construction of pharmaceutically and biologically active benzofuro[2, 3‐b]indoline compounds. Abstract :